Best Answer

The answer is 5x+3y.

(5 xs and 3 ys)

Q: How do you simplify x plus x plus x plus x plus y plus y plus y plus x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

It is the same. The equation "x + y" is the exact same as "x + y." There is no difference.

xy + x + y + 1 = (x + 1)(y + 1).

xz + x + yz + y = (x + y)(z + 1)

The answer is 20.you get this answer by reading the instructions.

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

Related questions

y-5x

3(x+y)

you can't simplify that anymore, you have to know what either x or y equals

Y plus Y = 2Y simplified

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

(x + y) / (x-1 + y-1) = (x + y) divided by ( 1/x + 1/y)Multiply numerator and denominator by 'xy' :xy (x + y) / (y + x)Then the whole thing falls apart, and we're left with:xy

You can't simplify it any further than 3x+2y+6z=24, unless you have been given values of x,y and z or other equations to find x,y and z.

3x

simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared

Given y = 2x + 4, plug in x = 42 and simplify: y = 2(42) + 4 y = 84 + 4 y = 88

6y

y2-x2 = (y+x)(y-x)